In-Silico Analysis of Secondary Metabolites that Inhibit Aldose Reductase Targeting Diabetic Retinopathy - Khatiwada, Ranju; Shrestha, Asmita; Gyawali, Kabita; Upadhyaya, Siddha Raj; Pradhan, Rezina; Phuyal, Ashish; KC, Sishir Bikram; Sharma, Khaga Raj; Parajuli, Niranjan (Journal of Institute of Science and Technology, 2025)
Diabetic retinopathy (DR) is a harmful microvascular consequence of diabetes. Aldose reductase, an enzyme involved in the polyol pathway during hyperglycaemic conditions, is responsible for DR. Some commercially available enzyme inhibitors, such as epalrestat, zenarestat, etc., are recommended medications to control pathophysiology; nevertheless, most of them have been unable to satisfy the criteria to be considered a good drug choice. This study aims to explore a pool of secondary metabolites associated with their impressive anti-diabetic properties because they are related to undesirable side of the commercial medications currently on the market. We screened the most potent aldose reductase inhibitor via a thorough in silico study, which has been reported as good in vitro activity against human aldose reductase and rat lens aldose reductase. High-throughput computational techniques were applied to study the potency of 90 metabolites against target proteins. In silico pharmacokinetics and toxicity were evaluated for screened metabolites with binding energy less than -9.0 kcal/mol obtained through the molecular docking method. Among selected metabolites, myrciacitrin IV exhibited the best binding affinity (-9.1 kcal/mol and -11.8 kcal/mol) with both proteins and displayed the least band gap energy (3.379 eV), comparable with the standard drug. Further, molecular dynamics (MD) simulation and Molecular Mechanics Generalised-Born Surface Area (MM/GBSA) investigations confirm myrciacitrin IV as a potent drug candidate targeting aldose reductase.